GEOCHEMISTRY OF GRORUDITES FROM THE EAST AZOV AREA - Dubyna, O.; Kryvdik, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the paper are presented the results of geochemical (ICP MS) investigation of the dyke analogues of alkali granites – grorudites that are widespread in the East Azov area. It is shown the most typical for considered grorudites are indicative such trace elements as Zr, Hf, Nb, Ta, REE, Sr and Ba. Two types grorudites are distinguished. By petrochemical and geochemical data these rocks are analogous to pantellerites and сomendites.